Brand New Social Life: Forms and Practices of Self-Promotion of Italian Teen Celebrities during the Pandemic - Caputo, Ylenia (Cinergie – Il Cinema e le altre Arti, 2022)
The pre-pandemic period saw the emergence of a new Italian audiovisual phenomenon: an innovative cinema and new television series, aimed at a specific target audience - the teenagers belonging to Generation Z. Italian teen dramas have led to the advent of a star system full of young actors and actresses. Their young age has facilitated their landing on social platforms, particularly on Instagram, where, to varying degrees, they are active and enjoy a large number of followers, mainly teenagers and young adults. The advent of the pandemic has drastically impacted the professional and daily lives of both actors and their audience, making social platforms the main compensatory forms for the lost sociality - for teenagers and young adults - as well as an important alternative stage for young actors. In this context, the paper aims to investigate the forms of self-promotion of the actors and actresses of the Italian teen world. Specifically, the analysis is focused on Benedetta Porcaroli, Beatrice Bruschi, Ludovica Martino, Federico Cesari, Rocco Fasano and Lorenzo Zurzolo, since they are among the best-known teen celebrities with the most numerous following body on social media. The reference time range starts from the first wave of Covid-19 in Italy (March 2020 - June 2020) and goes until the end of the second wave (October 2020 - Janauary 2021) in order to identify and analyze any differences between the two pandemic moments, in terms of representation, social engagement and professional activities of the examined actors.